Performance Evaluation of Routing Protocols in WiMax - Singh, Nidhi; Sangwan, Anil; Sehrawat, Harkesh; Malik, Rajat (International Journal of Computer Sciences and Engineering, 2025)
WiMax stands for World Wide Interoperability for Microwave Access. It is subjected on IEEE 802.16 air interface. WiMax enhances point to point and point to multipoint wideband wireless access and meets the requirements of millions of users demanding high speed at affordable cost. This paper presents four routing protocols namely Ad hoc On-Demand Distance Vector (AODV), Dynamic Source Routing (DSR), Optimized Link State Routing (OLSR), Zone Routing Protocol (ZRP) in different node density scenarios of (25, 50, 75 and 100). Their performance comparison is done by taking throughput, average jitter, and average end to end delay as performance metrics. All the scenarios are subjected on random way point mobility. Results are generated using QualNet simulator. This paper also presents a comparison of CBR and VBR traffic application taking protocol OLSR at 100 nodes.